European Guideline on IgG4-related digestive disease - UEG and SGF evidence-based recommendations - DUMAN, DENİZ (SAGE PUBLICATIONS INC, 2020)
The overall objective of these guidelines is to provide evidence-based recommendations for the diagnosis and management of immunoglobulin G4 (IgG4)-related digestive disease in adults and children. IgG4-related digestive disease can be diagnosed only with a comprehensive work-up that includes histology, organ morphology at imaging, serology, search for other organ involvement, and response to glucocorticoid treatment. Indications for treatment are symptomatic patients with obstructive jaundice, abdominal pain, posterior pancreatic pain, and involvement of extra-pancreatic digestive organs, including IgG4-related cholangitis. Treatment with glucocorticoids should be weight-based and initiated at a dose of 0.6-0.8 mg/kg body weight/day orally (typical starting dose 30-40 mg/day prednisone equivalent) for 1 month to induce remission and then be tapered within two additional months. Response to initial treatment should be assessed at week 2-4 with clinical, biochemical and morphological markers. Maintenance treatment with glucocorticoids should be considered in multi-organ disease or history of relapse. If there is no change in disease activity and burden within 3 months, the diagnosis should be reconsidered. If the disease relapsed during the 3 months of treatment, immunosuppressive drugs should be added.
Keywords: IgG4-related; digestive; disease; glucocorticoids; other organ involvement; biomarkers; autoimmune pancreatitis type 1; immune-related cholangitis; cancer; diabetes mellitus; IMMUNOGLOBULIN G4-RELATED DISEASE; TYPE-1 AUTOIMMUNE PANCREATITIS; FINE-NEEDLE-ASPIRATION; LONG-TERM OUTCOMES; PRIMARY SCLEROSING CHOLANGITIS; EMISSION TOMOGRAPHY/COMPUTED TOMOGRAPHY; CONSENSUS DIAGNOSTIC-CRITERIA; SERUM IGG4 LEVELS; STEROID-THERAPY; INTERNATIONAL-CONSENSUS